Feeding compact bulges and supermassive black holes with low angular momentum cosmic gas at high redshift - Dubois, Y; Pichon, C; Haehnelt, M; Kimm, T; Slyz, A; Devriendt, J; Pogosyan, D (2012)
We use cosmological hydrodynamical simulations to show that a significant fraction of the gas in high redshift rare massive haloes falls nearly radially to their very centre on extremely short time-scales. This process results in the formation of very compact bulges with specific angular momentum a factor of 5-30 smaller than the average angular momentum of the baryons in the whole halo. Such low angular momentum originates from both segregation and effective cancellation when the gas flows to the centre of the halo along well-defined cold filamentary streams. These filaments penetrate deep inside the halo and connect to the bulge from multiple rapidly changing directions. Structures falling in along the filaments (satellite galaxies) or formed by gravitational instabilities triggered by the inflow (star clusters) further reduce the angular momentum of the gas in the bulge. Finally, the fraction of gas radially falling to the centre appears to increase with the mass of the halo; we argue that this is most likely due to an enhanced cancellation of angular momentum in rarer haloes which are fed by more isotropically distributed cold streams. Such an increasingly efficient funnelling of low angular momentum gas to the centre of very massive haloes at high redshift may account for the rapid pace at which the most massive supermassive black holes grow to reach observed masses around 10 9M ⊙ at an epoch when the Universe is barely 1 Gyr old. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.